Implementasi Model Instalasi Pengelolaan Air Limbah dengan Menambahkan Berbentuk (L) Setiap Tangki - Musawantoro, Muhammad; Syarif, Erman; Salim, Muhammad Arfin Muh; Zaenal, Faisal Akbar (LaGeografia, 2020)
The importance of this research is to provide a new development in the form of the development of the addition of L-shaped pipe accessories added to the pipe in each tank from previous studies, Implementation of previous research has not been maximized when used in the kitchen of Makassar Tourism Polytechnic so that modifications are made, because it is not there is a difference in waste from each tank, furthermore this research uses research and development research methods with the development of existing models by not build the new construction from scratch, while the development of this research is to add pipes in the form (L) or L-shaped pipe attached to the tank number one (1) as the first tank for waste that is disposed of often containing foam soap, fat and heavy sediments, then in the second tank (2) which already does not contain foam, grease, and heavy sediments, reattach the L pipe to reduce the content is what if it still exists, then add sand material, and gravel, as the dissolved material Chemical Oxygen Demands (COD) dissolved in the third tank (3) before being channeled into the public sewer. This research recommends that before disposal of liquid waste from processed food, it is better to do the separation of the sediment contained in the liquid waste and then to develop it further to get more perfect results, especially the criteria for Wastewater Clarity.